The Research of Thomas P. Branson - Eastwood, M.G.; Gover, A.R. (Symmetry, Integrability and Geometry: Methods and Applications, 2008)
The Midwest Geometry Conference 2007 was devoted to the substantial mathematical legacy of Thomas P. Branson who passed away unexpectedly the previous year. This contribution to the Proceedings briefly introduces this legacy. We also take the opportunity of recording his bibliography. Thomas Branson was on the Editorial Board of SIGMA and we are pleased that SIGMA is able to publish the Proceedings.